Ancylostoma Induced Acute Haemorrhagic Gastroenteritis in a Male Adult Kanni Dog: An Uncommon Incidence - Subramanian; Ganapathy, Selvaraju (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Ancylostoma caninum is the major cause of canine hookworm disease in most tropical and subtropical regions of the world and anaemia is the main pathological effect caused by blood sucking activity of the worms (Umeakuana et al., 2020). The disease is more often seen in young puppies or dogs under one year of age, by transmammary route of infection and adult dogs are mostly asymptomatic owing to their acquired immunity. Nevertheless, the dog may show iron deficiency and develop a microcytic hypochromic anaemia. Severe anaemia is commonly encountered in puppies and could be successfully treated by appropriate therapy, which includes blood transfusion (Jasmin et al. 2020). Hence, severe anaemia requires fecal examination and presence of many eggs in feces is suggestive of acute ancylostomosis, though clinical signs could be observed during the prepatent phase itself (Lefkaditis, 2001). This document reports an unusual case of ancylostoma induced acute haemorrhagic gastroenteritis and its management in an adult male Kanni dog.